1990
DOI: 10.1002/art.1780330714
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous gamma globulin therapy in systemic juvenile rheumatoid arthritis

Abstract: Intravenous (IV) gamma globulin has been successfully used as replacement therapy for antibody‐deficient patients and, more recently, in the treatment of autoimmune diseases such as idiopathic thrombocytopenic purpura, myasthenia gravis, and Kawasaki disease. In view of the successful treatment of these diseases, we initiated a pilot study of the effect of IV gamma globulin in systemic juvenile rheumatoid arthritis (JRA). Eight patients with active systemic JRA that was unresponsive to first‐line agents, secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 25 publications
0
16
1
1
Order By: Relevance
“…Recent studies found only limited benefit of IVIG during the chronic course of juvenile-onset Still's disease [17,18]. But this does not contradict our results, since we used IVIG as an emergency treatment during fulminant macrophage activation in adults.…”
Section: Discussioncontrasting
confidence: 44%
“…Recent studies found only limited benefit of IVIG during the chronic course of juvenile-onset Still's disease [17,18]. But this does not contradict our results, since we used IVIG as an emergency treatment during fulminant macrophage activation in adults.…”
Section: Discussioncontrasting
confidence: 44%
“…Based on the work of Silverman et al [5], we decided to treat her with intravenous immunoglobulin (IVIG). She received infusions of 1.5 g/kg every 2 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some patients can be adequately treated with cytotoxic drugs including azathioprine, chlorambucil, cyclophosphamide (5) and lately, methotrexate (16-1 8). Recently, a few patients with juvenile-onset Still's disease have been treated with novel therapeutic modalities, including y-interferon ( 1 9), intravenous y-globulin (20) and cyclosporin (21). Such treatments have not yet been used for patients with adult Still's disease, but they certainly offer the possibility of future application especially to the refractory cases.…”
Section: Discussionmentioning
confidence: 99%